2011
DOI: 10.5194/acp-11-1791-2011
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of tropospheric BrO columns using GOME-2 satellite data

Abstract: Abstract.Measurements from the GOME-2 satellite instrument have been analyzed for tropospheric BrO using a residual technique that combines measured BrO columns and estimates of the stratospheric BrO content from a climatological approach driven by O 3 and NO 2 observations. Comparisons between the GOME-2 results and BrO vertical columns derived from correlative ground-based and SCIAMACHY nadir observations, present a good level of consistency. We show that the adopted technique enables separation of stratosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
274
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(308 citation statements)
references
References 77 publications
14
274
2
1
Order By: Relevance
“…Based on the oxygen and nitrogen isotope composition of airborne nitrate at DDU, concluded to an absence of significant implication of BrO in the formation of nitric acid at this site, contrarily to what is usually observed in the Arctic where high levels of BrO are measured at polar sunrise (Morin et al, 2008). All these observations are consistent with a less efficient bromine chemistry in East compared to West Antarctica due to a less sea-ice coverage, as also supported by GOME-2 satellite observations of the tropospheric BrO column (Theys et al, 2011;Legrand et al, 2016a). Additionally, air masses originating from the Antarctic plateau prevailed (62 ± 23 %, Fig.…”
Section: The Ice-covered Ocean As a Sink For Hg(0) In Springsupporting
confidence: 75%
“…Based on the oxygen and nitrogen isotope composition of airborne nitrate at DDU, concluded to an absence of significant implication of BrO in the formation of nitric acid at this site, contrarily to what is usually observed in the Arctic where high levels of BrO are measured at polar sunrise (Morin et al, 2008). All these observations are consistent with a less efficient bromine chemistry in East compared to West Antarctica due to a less sea-ice coverage, as also supported by GOME-2 satellite observations of the tropospheric BrO column (Theys et al, 2011;Legrand et al, 2016a). Additionally, air masses originating from the Antarctic plateau prevailed (62 ± 23 %, Fig.…”
Section: The Ice-covered Ocean As a Sink For Hg(0) In Springsupporting
confidence: 75%
“…Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere. Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelsupporting
confidence: 50%
“…The global model simulations reported here predict average mixing ratios of ∼ 0.5 ppt for BrO and ∼ 1 ppt for IO during SOS and thus underpredict BrO but perform well for IO. The underprediction of BrO at the Cape Verde Atmospheric Observatory results from recent model updates which exclude emissions of bromine species from sea-salt debromination (Schmidt et al, 2016) in order to provide improved agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free tro- posphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). If sea-salt debromination were included, daytime mixing ratios of BrO at the Cape Verde Atmospheric Observatory would be approximately 2 ppt, as shown by Parella et al (2012) and Schmidt et al (2016), and thus in closer agreement to the observations.…”
Section: Global Modelmentioning
confidence: 99%
“…Holmes et al (2006) first suggested Br atoms could be the main Hg 0 oxidant on a global scale, with Br originating principally from photochemical decomposition of bromoform emitted by phytoplankton (Yang et al, 2005). More recent observations of background tropospheric BrO point to ubiquitous Br radical chemistry in the troposphere (Theys et al, 2011;Wang et al, 2015). Recent aircraft observations of Hg II and BrO over the southeastern US are consistent with Br atoms acting as the main Hg 0 oxidant (Gratz et al, 2015;Shah et al, 2016).…”
Section: Introductionmentioning
confidence: 65%